Facile Construction of Hydantoin Scaffolds via a Post-Ugi Cascade Reaction - Xu, Zhi-Gang; Ding, Yong; Meng, Jiang-Ping; Tang, Dian-Yong; Li, Yong; Lei, Jie; Xu, Chuan; Chen, Zhong-Zhu (Synlett, 2018)
A small series of hydantoins was efficiently synthesized via a two-step Ugi/cyclization reaction sequence using alkyne group as a leaving group under basic conditions. This microwave-assisted one-pot cyclization strategy could be applicable to other multicomponent reactions (MCRs) for synthesizing bioactive and drug-like hydantoins.
Keywords: hydantoins; multicomponent reactions (MCRs); one-pot; alkyne group; leaving group